Rubber Based Bionanocomposites : Preparation - Visakh P. M. (Advanced Structured Materials, 2017)
Leading researchers from industry, academy, government and private research institutions across the globe have contributed to this book, which presents all types of rubber blend composites based on biomaterials as well as nanocomposites. It discusses the fundamental preparation methods of these materials and summarizes many of the latest technical research advances, offering an essential guide for academics, researchers, scientists, engineers and students alike. .